EVALUASI POTENSI SUMBERDAYA AIR UNTUK PENGEMBANGAN INDUSTRI DI KOTA BONTANG, KALIMANTAN TIMUR - Herlambang, Arie (Jurnal Air Indonesia, 2014)
The total population Bontang in 2014 is around 187,346 peoples. With the level of domestic water demand of 110 liters /person/day, the water needs of the city for at least Bontang 238.52 liters/sec. Currently for the needs of the community water supply received from the local water company with a capacity of 80 liters/sec, and It will be developed further to 250 liters/second in 2015. There are two big industries that need huge of water, namely LNG and Fertilizers Factory. Factory of East Kalimantan (PKT) need additional water supply around 1000 m3/h or (166.67 liters/sec) with the specifications for the Water Industry and 200 m3/h will be used to supply the needs of water for 21 818 inhabitants. Bontang city water source can be derived from groundwater, rivers, and rain water storage (reservoirs of water). In recent decades Bontang relied upon groundwater for water supply industry and some communities, the rest use river water and rain water tandah. With a very heavy rainfall (> 2500 mm / year), then the making of ponds in large quantities can help to reserve water in the future. For the purposes of future water supplies, it would require an asessment of all potential water resources utilization and planning for the use of adapted to the urban development plan. Water recycling of domestic waste is also a potential source of fresh water in the future, especially for industrial use. The drainage system needs to be directed at a large holding pond located in a low area, before going into the sea. The rain that fell in the city drained and collected would be of potential if utilized. In short-term utilization of water of the Bontang river is very of potential, given its location in the city center and is one of the many watersheds in Bontang, causing floods in the rainy season. Control and management of water is needed to support the use of river water.Keywords: Water resources, Water Demand, Water Supply, and Water Balance